METHODS OF TEACHING THE RUSSIAN LANGUAGE IN HIGHER EDUCATIONAL INSTITUTIONS - Abaeva Nino Chermenovna; Zaitova Ozoda Yusupovna (Social science and innovation, 2024)
This scientific article discusses modern approaches and methods of teaching the Russian language in higher educational institutions (HEIs). The authors analyze the features of the educational process adapted to the needs of students and highlight the key components of successful methods of teaching the Russian language in the context of modern higher education